BS EN 15634-3. Foodstuffs. Detection of food allergens by molecular biological methods. Part 3. Hazelnut (Corylus avellana). Qualitative detection of a specific DNA sequence in chocolate by real-time PCR (15th November 2021) - British Standards Institution,
No abstract available